DESAIN DAN UJI COBA LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS SCIENCE, TECHNOLOGY, ENGINEERING AND MATHEMATICS (STEM) DENGAN MENGGUNAKAN MEDIA MOODLE PADA MATERI ASAM BASA - Vika Eka Yunita; lisa utami (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2021)
AbstractThis research was instigated by student workbook integrating Chemistry material with STEM that was not yet available.  Since the outbreak of COVID-19, WHO has recommended to temporarily suspend activities that could potentially cause crowds. Therefore, the learning process is carried out online during COVID-19 emergency period.  One alternative supporting the online learning process was by using Moodle learning media in which there was Science, Technology, Engineering, and Mathematics (STEM) based student workbook.  This research aimed at knowing the validity and practicality levels of STEM based student workbook on Acid Base lesson.  It was Research and Development (R&D) with Borg and Gall development model, but it was only until the fifth stagerevising the initial form of the product.  This research was conducted to the twelfth-grade students of MIPA 4 at State Senior High School 2 Tambang.  Interview, questionnaire, and documentation were the techniques of collecting the data.  The research findings showed that STEM based student workbook got the validity percentages from media and material experts continuously 93.75% and 82.2% with very valid criteria, while the validity percentage of Moodle learning media was 78.46%.   The practicality percentage of the workbook was 90% with very practical criterion, and the workbook got positive and good student response with the percentage 90%.Keywords: Student Workbook, STEM, Acid Base, Moodle Learning Media